Estudios subalternos postransicionales como propuesta de acercamiento comparativo a la narrativa polaca y española contemporánea - Kłosińska-Nachin, Agnieszka (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The paper aims to develop a comparative perspective that allows the reader toexplore the traces of authoritarian systems in contemporary Polish and Spanish culture.The point of departure is the research of Polish scholars from the Post-Dependence StudiesCentre, who examine Polish culture with postcolonial tools adapted to the post-communistcontext. From there, the article attempts to formulate a methodological framework – the socalledpost-transitional subaltern studies – applicable to post-Franco and post-communistculture, particularly the presence of subaltern characters in contemporary cultural texts. Inaccordance with the proposed methodology, the author analyses two novels, namely Visióndel ahogado (1977) by Juan José Millás and Czytadło (1992) by Tadeusz Konwicki, in which itis possible to detect similar panoptic strategies concomitant with the recourse to violence.